2004
DOI: 10.1021/ci049747p
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Electronic Structure of Organic Chemicals Using Semiempirical and Ab Initio Methods for Development of Toxicological QSARs

Abstract: The quality of quantitative structure-activity relationship (QSAR) models depends on the quality of their constitutive elements including the biological activity, statistical procedure applied, and the physicochemical and structural descriptors. The aim of this study was to assess the comparative use of ab initio and semiempirical quantum chemical calculations for the development of toxicological QSARs applied to a large and chemically diverse data set. A heterogeneous collection of 568 organic compounds with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 32 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…To compare the robustness of different methods (ab initio and semi-empirical) for calculation of electronic descriptors, a best subset analysis was performed (outliers not excluded) with log K ow and two sets of descriptors [4]. The authors found that the more computer-intensive ab initio calculations do not offer significant improvement when used in models for fish toxicity but different descriptors (suggesting different posteriori mechanistic interpretation) were selected.…”
Section: Examples Of Statistically Derived Qsarsmentioning
confidence: 99%
“…To compare the robustness of different methods (ab initio and semi-empirical) for calculation of electronic descriptors, a best subset analysis was performed (outliers not excluded) with log K ow and two sets of descriptors [4]. The authors found that the more computer-intensive ab initio calculations do not offer significant improvement when used in models for fish toxicity but different descriptors (suggesting different posteriori mechanistic interpretation) were selected.…”
Section: Examples Of Statistically Derived Qsarsmentioning
confidence: 99%
“…Successful examples of more novel applications of MLR are in the papers: Netzeva et al, 2005;Ren S., 2003;Ghafourian and Cronin, 2005. In some recent publications, particular attention is devoted to model validation for predictivity and chemical domain of applicability, as well as to the descriptor interpretation, thus to the model development according to all the OECD Principles Pavan et al, 2006).…”
mentioning
confidence: 99%
“…Also, the nitro substituent seems to be more toxic than chlorine substituent. For the purpose of comparison, the 15 min Chlorella vulgaris EC 50 values of anilines (Netzeva et al 2004) and the 96 h fathead minnow LC 50 values of anilines and phenols (Netzeva et al 2005) are also shown in Table 1. When the toxicity of five anilines on bacteria was compared with those from C. vulgaris, all the chemicals tested exhibited higher toxicity on bacteria than on C. vulgaris.…”
Section: Resultsmentioning
confidence: 99%